Método alternativo para determinação de fósforo e enxofre em biodiesel - VIÉGAS, Helmara Diniz Costa (2017)
The importance of quality control of biodiesel has motivated the development of alternative methods, especially those of low operational cost that are of significant importance in order to assist in strict quality control regarding to official analytical parameters. Although present in low concentrations, phosphorus affects catalytic conversion in the exhaust system of diesel engines and increases the generation of gaseous pollutants. Like phosphorus, sulfur is also a typical poison of catalysts and therefore affects catalytic converters, is an undesirable element in any fuel due to the corrosive action of its compounds and the formation of toxic gases that occurs during combustion. In order to develop, optimize and apply electrochemical procedures as an alternative method for determination of phosphorus and sulfur in biodiesel some electrochemical sensors were evaluated. For the determination of sulfur, the glassy-carbon electrode modified with bismuth film with LOD 4,28 X 10-8 mol L-1 and de LOQ 1,43 X 10-7 mol L-1 was evaluated and for the phosphorus the glassy-carbon electrode modified with Cobalt nanoparticles (Co[Fe(CN)5NO]) with LOQ de 7,48 x 10-5 mol L-1 and LOQ de 2,52 x 10-4 mol L -1 was evaluated, as well as was evaluated the modification with Cobalt Hexacyanoferrate (Co3[Fe(CN)6]2 - CoCHF) with LOD de 2,81x10-4 mol L-1 and LOQ de 9,37 x10-4 mol L-1 . The CoCHF film was deposited electrochemically, while the modification of the nanoparticles was performed with the deposition of an aliquot of ethanolic solution of nafion and nanoparticle on the surface of the electrode. The response of these sensors was studied by voltammetric techniques, being applied in Biodiesel. Cobalt nanoparticles were characterized by Scanning Electron Microscopy, showing 100 nm hexagonal particles, and by X-ray Dispersive Energy, identifying the species (cobalt, iron, carbon, nitrogen, oxygen) present in the structure of the material. The results obtained demonstrate that the sensors used presented good analytical response for the species of interest.